MENEGUHKAN SPIRIT KEMASLAHATAN: MASJID, PEMBERDAYAAN DAN TRANSFORMASI SOSIAL - Ahmad Arif Widianto; Rose Fitria Lutfiana (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
Government development programs often encounter obstacles, creating new problems in society. In this context, community empowerment initiatives emerged that took advantage of local institutions that were considered to have bargaining power and were effective in society. Mosques as part of social institutions are also proven capable of carrying out their social functions as facilitators of empowerment. This article aims to map how mosque-based empowerment models and their achievements so far. Through a literature review, this article sorts data from various articles published in 2010-2020 that discuss the topic of mosques and empowerment. This article shows that mosques have various social functions that can fill the void in the role of government in serving the needs of the community. Through their bargaining position, the mosque becomes an effective media or facilitator created social transformation. The models of empowerment by mosques are chosen based on the types of needs and conditions of the community including developing potential, strengthening and protecting the community. This strengthens the social function of mosques which are adaptive and responsive to social needs when government efforts are ineffective.